Review on the roles of specific cell-derived exosomes in Alzheimer's disease - Zou, Yutong; Mu, Danni; Ma, Xiaoli; Wang, Danchen; Zhong, Jian; Gao, Jing; Yu, Songlin; Qiu, Ling (Frontiers in Neuroscience, 2022)
Alzheimer’s disease (AD) is the sixth leading cause of death worldwide and cannot be effectively cured or prevented; thus, early diagnosis and intervention are important. The importance of exosomes, membrane-bound extracellular vesicles produced in the endosome of eukaryotic cells, in the development, diagnosis, and treatment of AD has been recognized; however, their specific functions remain controversial and even unclear. With the development of exosome extraction, isolation, and characterization, many studies have focused on exosomes derived from different cells and body fluids. In this study, we summarized the roles of exosomes derived from different body fluids and cells, such as neuron, glial, stem, and endothelial cells, in the development, diagnosis, monitoring, and treatment of AD. We also emphasize the necessity to focus on exosomes from biological fluids and specific cells that are less invasive to target. Moreover, aside from the concentrations of classic and novel biomarkers in exosomes, the size and number of exosomes may also influence early and differential diagnosis of AD.